A Novel Chemically Modified Curcumin "Normalizes" Wound-Healing in Rats with Experimentally Induced Type I Diabetes: Initial Studies. (13th April 2016) - Zhang, Yazhou; McClain, Steve A.; Lee, Hsi-Ming; Elburki, Muna S.; Yu, Huiwen; Gu, Ying; Zhang, Yu; Wolff, Mark; Johnson, Francis; Golub, Lorne M.
Abstract : Introduction . Impaired wound-healing in diabetics can lead to life-threatening complications, such as limb amputation, associated in part with excessive matrix metalloproteinase- (MMP-) mediated degradation of collagen and other matrix constituents. In the current study, a novel triketonic chemically modified curcumin, CMC2.24, was tested for efficacy in healing of standardized skin wounds in streptozotocin-induced diabetic rats. Initially, CMC2.24 was daily applied topically at 1% or 3% concentrations or administered systemically (oral intubation; 30 mg/kg); controls received vehicle treatment only. Over 7 days, the diabetics exhibited impaired wound closure, assessed by gross and histologic measurements, compared to the nondiabetic controls. All drug treatments significantly improved wound closure with efficacy ratings as follows: 1% 2.24 > systemic 2.24 > 3% 2.24 with no effect on the severe hyperglycemia. In subsequent experiments, 1% CMC2.24 "normalized" wound-healing in the diabetics, whereas 1% curcumin was no more effective than 0.25% CMC2.24, and the latter remained 34% worse than normal. MMP-8 was increased 10-fold in the diabetic wounds and topically applied 1% (but not 0.25%) CMC2.24 significantly reduced this excessive collagenase-2; MMP-13/collagenase-3 did not show significant changes. Additional studies indicated efficacy of 1% CMC2.24 over more prolonged periods of time up to 30 days.